Simultaneous determination of Bingham material parameters using a ball probe concrete rheometer. Issue 1 (25th January 2021) - Gerland, Florian; Schomberg, Thomas; Wetzel, Alexander; Middendorf, Bernhard; Wünsch, Olaf
Abstract: A new evaluation method allowing direct determination of the Bingham parameters from ball probe rheometers. A non‐linear relationship between the direct measured variables and the material parameters is revealed through numerical parameter studies. The method was validated on two devices of the ball probe type with different dimensions. Comparison with other methods showed good agreement. It is pointed out how the evaluation method can be transferred to devices having other dimensions by performing a limited number of straightforward calibration experiments. This work closes the gap between established ball probe rheometer evaluations and objective material parameters. Objective material parameters can be extracted from every ball probe rheometer. Even existing data can be converted.